Wallace Stevens : An Anatomy of Figuration - Nassar, Eugene Paul (University of Pennsylvania Press, 1965)
This book presents for the first time a thorough study of the imagery in Wallace Stevens's poetry and the patterns which these images form. Heretofore, most discussions of Stevens's work presupposed an understanding of the difficult and bizarre surface imagery and dealt mainly with broad generalizations which often left the student of Stevens's poems unsatisfied. The brilliant surface of the poems, the detailed imagery of specific passages, is here examined clearly and systematically. The images, indexed at the back of the book, are examined in four natural groups: Figures of the Mind, of Disorder, of Order, and of Change. The last half of the book is concerned with close analyses of some longer poems of Stevens's using the information gleaned from the "anatomy" of the first half.